An impedimetric molecularly-imprinted biosensor for Interleukin-1 determination, prepared by in-situ electropolymerization on carbon screen-printed electrodes - Cardoso, Rita (2019)
This work reports the first electrochemical molecularly imprinted polymer (MIP) sensor for Interleukin-1beta (IL-1) detection, based on modified commercial screen-printed carbon electrode (SPCE) was successfully demonstrated. For this purpose, the carbon support was modified with a PEDOT/4-aminothiophenol layer prior to the MIP film to enhance sensitivity and signal stability. The MIP layer was constructed on top of this by electropolymerization of Eriochrome black T (EBT) in the presence of IL-1. The several steps of the biosensor assembly was followed by Raman spectroscopy and electroanalytical techniques. Using electrochemical impedance spectroscopy (EIS), a linear response in the range of 60 pM to 600nM, with a LOD of 1.5 pM with (S/N=3) was obtained in neutral PBS. Selectivity tests of the MIP biosensor made in spiked synthetic serum samples as well as against other structurally related (Myoglobin, of similar shape and size) or competing compounds (Immunoglobulin G, also present in the human serum) confirmed the good selectivity of the biosensor. Overall, the biosensor described herein has the potential to provide a simple and quick way for on-site screening of IL-1, with low sample/reagent consumption and enabling direct serum analysis, which constitutes a valuable alternative to other conventional methods.